Organization of educational process in the course «Using IMIAS of Moscow in the work of medical personnel» - G. V. Kuznetsova (Сеченовский вестник, 2015)
The article summarizes the experience of teaching the subject «Using IMIAS of Moscow with medical personnel» at the Medical College № 1 of Moscow Health Department. The author lists the forms of theoretical and practical training, promotes better learning outcomes, as well as the types of extracurricular independent works. Usefulness of this material may be not only in the teaching of the above-mentioned disciplines, but also in the classroom, related to the study of any application software.